Vocabulary knowledge components: knowledge, acquisition and conceptualisation - González-Fernández, Beatriz (2018)
Vocabulary knowledge is a multifaceted construct for which complete command comprises mastering various types of knowledge. Achieving this full mastery is deemed challenging and problematic for second language learners, and yet it is key for successful and appropriate language use (Webb & Nation, 2017). By understanding how these various kinds of knowledge behave and relate, practitioners can better systematise when and how they are introduced to the students, and thus facilitate the overall vocabulary learning process. Nevertheless, little is known about how these multiple types of word knowledge are acquired by learners of a second/foreign language. This thesis attempts to contribute to bridging this gap by empirically exploring the knowledge, acquisition and conceptualisation of overall vocabulary knowledge in second languages. Five studies are devoted to this aim. Study 1 examined the knowledge and order of acquisition of four different components of vocabulary knowledge (form–meaning link, collocations, derivatives and multiple meanings) in recall and recognition. It shows that those components vary considerably in their difficulty for second language (L2) learners, and implicational scaling analysis revealed that a consistent order of acquisition of these components can be established. Study 2 investigated how various factors typically identified as influencing vocabulary learning affect the mastery of those four word knowledge components. The results suggest that cognateness status of the target words has the strongest effect on knowledge of most vocabulary aspects by Spanish learners of L2 English, followed by frequency and proficiency. Importantly, this cognate influence raised the question of whether the order of acquisition of word knowledge components retrieved in Study 1 was unique to L2 English learners of cognate languages. Study 3 explored the theoretical conceptualisation of vocabulary knowledge by attempting to provide empirical support for its multidimensionality. Structural equation modelling analyses exposed that the various types of vocabulary knowledge were so interconnected that they could not be considered separate dimensions. This finding suggests that the different aspects of vocabulary knowledge are better seen as various word knowledge difficulty levels that comprise a unidimensional construct. Finally, Studies 4 and 5 tried to provide generalisability to the previous findings by replicating Studies 1 and 3, respectively, with Chinese L2 learners of English. Study 4 investigated the hypothesis that the order of acquisition outlined in Study 1 for Spanish learners depended partially on the cognate status of the participants’ language. The implicational scaling analysis with the non-cognate Chinese population, however, corroborated the order of acquisition of vocabulary aspects previously suggested, indicating that a universal vocabulary acquisition order might exist. Study 5 also confirmed the finding that vocabulary knowledge is not empirically multidimensional. In addition, it provided evidence for the fact that the vocabulary knowledge construct functions similarly across the Chinese and Spanish learners of English as a unidimensional concept. Taken together, the results presented in this thesis support the notion that mastering the various components involved in word knowledge is a slow and incremental process, and demonstrate that some of them seem to be consistently acquired before others. Nonetheless, the findings also suggest that these different types of word knowledge cannot be considered separate dimensions in the learners’ mental lexicon, and thereby the multidimensional structure of vocabulary knowledge might need to be reconsidered. Overall, while more research is needed, these findings offer useful insights for the learning and teaching of vocabulary in a more systematic and efficient manner.